2013
DOI: 10.1007/s12192-012-0393-8
|View full text |Cite
|
Sign up to set email alerts
|

Daily and seasonal changes in heat exposure and the Hsp70 level of individuals from a field population of Xeropicta derbentina (Krynicki 1836) (Pulmonata, Hygromiidae) in Southern France

Abstract: The Mediterranean land snail Xeropicta derbentina forms huge populations in Southern France. In order to characterize heat exposure and the induction of the 70-kD heat shock protein (Hsp70) response system during the life cycle of this snail, a selected population from the Vaucluse area, Provence, was investigated encompassing the issues of morphological life cycle parameters (shell size and colouration), the daily courses of heat exposure at different heights above the ground, of shell temperature, and that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…Among these pale individuals lower percentages of individuals were observed which were characterized by a darkly pigmented banding of the shell and which can be categorized according to the banding pattern described in previous studies (Di Lellis et al 2012;Dieterich et al 2012;Dittbrenner et al 2009;Köhler et al 2009). …”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Among these pale individuals lower percentages of individuals were observed which were characterized by a darkly pigmented banding of the shell and which can be categorized according to the banding pattern described in previous studies (Di Lellis et al 2012;Dieterich et al 2012;Dittbrenner et al 2009;Köhler et al 2009). …”
Section: Introductionmentioning
confidence: 77%
“…In its adult state, X. derbentina reaches shell sizes up to 16 mm in diameter. This annual species (Dieterich et al 2012;Kiss et al 2005) can often be found in areas with scarce vegetation, at the borders of agricultural areas and along roads. The ability to climb vertical objects can not only be seen as a way to protect these snails from overheating in consequence of high ground temperatures, as postulated by different authors (Cowie 1985;Pomeroy 1968).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations